Encuesta sobre la Corona - Aragón Reyes, Manuel; Expósito Gómez, Enriqueta; de la Iglesia Chamarro, Asunción; Oliver Araujo, Joan; Pascual Medrano, Amalia; Porras Ramírez, José María; Rollnert Liern , Göran; Sánchez Navarro, Ángel J. (Teoría y Realidad Constitucional, 2023)
Encuesta sobre la Corona